Nordisk prostitusjonspolitikk : ser vi framveksten av en nordisk modell? - Skilbrei, May-Len; Holmström, Charlotta (Malmö högskola, Institutionen för socialt arbete (SA), 2010)
The prostitution policies implemented in the Nordic countries have gone through major changes over the past 15 years. A change that has drawn a lot of attention, both within the Nordic region and internationally, is the introduction of prohibitions against the purchase of sexual acts and services. Sweden, Norway and Iceland have introduced such prohibitions, and Finland has criminalised buying sex from victims of trafficking or persons involved in pimp-organised prostitution. The laws applied to prostitution have to be understood in light of how prostitution is defined and dealt with as a social problem, and their existence explained by ideological developments and developments in the prostitution market. The fact that several countries have implemented similar legal reforms does not mean that the Nordic countries have a consistent approach to prostitution. In this article we describe how prostitution is handled in the Nordic countries and discuss the question as to whether one can now say that there is a common Nordic prostitution regime.